Challenges Encountered in Taking Modular Distance Learning Mode: A Case of Senior High School (SHS) Students - Tenedero, Cynic; Valencia, Irish; Villenes, Rejulios; Panti, Rose Ann (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
This is descriptive correlational research that evaluates the challenges experienced by Senior High School (SHS) students of Lopez National Comprehensive High School, Quezon Province, Philippines in taking modular distance learning mode. Pearson R was used to assess the significant relationship between the demographic profile of the respondents and the challenges experienced by SHS students in taking modular distance learning mode. The respondents of this study were sixty-nine (69) Grade 12 SHS students who experienced taking modular distance learning mode. A self-made questionnaire was used. It was found out that independent learning practices, motivation and focus, learning intervention and support and learning space and management were significantly correlated to demographic profile and the challenges experienced in taking modular distance learning mode, thus, the null hypothesis is rejected. It is evident that respondents hardly understand the lesson in modular distance learning mode because the instruction in the self-learning module is not clear. SHS students spent more time using gadgets than studying. Moreover, the study area had distractions and noise and most parents of SHS students did not talk about the problems they encountered in the self-learning module. It is recommended to coordinate with the parents to create a learning intervention at home, and also, teachers should provide books to act as supplementary materials. Hence, this will introduce to the academy a possible enhancement program to the institution that will allow us to utilize different learning strategy and gamification in teaching considering the post pandemic learning mode.